A Dynamic 3D Aggregate-Based System for the Successful Expansion and Neural Induction of Human Pluripotent Stem Cells - Miranda, Cláudia C.; Akenhead, Michael L.; Silva, Teresa P.; Derr, Michael A.; Vemuri, Mohan C.; Cabral, Joaquim M. S.; Fernandes, Tiago G. (Frontiers in Cellular Neuroscience, 2022)
The demand for large cell numbers for cellular therapies and drug screening applications requires the development of scalable platforms capable of generating high-quality populations of tissue-specific cells derived from human pluripotent stem cells (hPSCs). Here, we studied the ability of Gibco StemScale PSC Suspension Medium to promote the efficient expansion of hPSC cultures as aggregates grown in suspension. We tested human induced pluripotent stem cell (hiPSC) growth in 6-well plates (on orbital shaker platforms) and single-use vertical-wheel bioreactors for a total of 3 consecutive passages. Up to a 9-fold increase in cell number was observed over 5 days per passage, with a cumulative fold change up to 600 in 15 days. Additionally, we compared neural induction of hiPSCs by using a dual SMAD inhibition protocol with a commercially available neural induction medium, which can potentially yield more than a 30-fold change, including neural progenitor induction and expansion. This system can also be adapted towards the generation of floor plate progenitors, which yields up to an 80-fold change in cell number and generates FOXA2-positive populations. In summary, we developed platforms for hiPSC expansion and neural induction into different brain regions that provide scalability towards producing clinically relevant cell numbers.